The clinical epidemiology of sickle cell anemia In Africa. Issue 3 (18th December 2017) - Macharia, Alex W.; Mochamah, George; Uyoga, Sophie; Ndila, Carolyne M.; Nyutu, Gideon; Makale, Johnstone; Tendwa, Metrine; Nyatichi, Emily; Ojal, John; Shebe, Mohammed; Awuondo, Kennedy O.; Mturi, Neema; et al.
Abstract: Sickle cell anemia (SCA) is the commonest severe monogenic disorders of humans. The disease has been highly characterized in high‐income countries but not in sub‐Saharan Africa where SCA is most prevalent. We conducted a retrospective cohort study of all children 0–13 years admitted from within a defined study area to Kilifi County Hospital in Kenya over a five‐year period. Children were genotyped for SCA retrospectively and incidence rates calculated with reference to population data. Overall, 576 of 18, 873 (3.1%) admissions had SCA of whom the majority (399; 69.3%) were previously undiagnosed. The incidence of all‐cause hospital admission was 57.2/100 person years of observation (PYO; 95%CI 52.6–62.1) in children with SCA and 3.7/100 PYO (95%CI 3.7–3.8) in those without SCA (IRR 15.3; 95%CI 14.1–16.6). Rates were higher for the majority of syndromic diagnoses at all ages beyond the neonatal period, being especially high for severe anemia (hemoglobin <50 g/L; IRR 58.8; 95%CI 50.3–68.7), stroke (IRR 486; 95%CI 68.4–3, 450), bacteremia (IRR 23.4; 95%CI 17.4–31.4), and for bone (IRR 607; 95%CI 284–1, 300), and joint (IRR 80.9; 95%CI 18.1–362) infections. The use of an algorithm based on just five clinical features would have identified approximately half of all SCA cases among hospital‐admitted children with a number needed to test to identify each affected patient of only fourteen. Our study illustrates the clinical epidemiology of SCA in a malaria‐endemic environment without specific interventions. The targeted testing of hospital‐admitted children using the Kilifi Algorithm provides a pragmatic approach to early diagnosis in high‐prevalence countries where newborn screening is unavailable.